Draft Seventh Five Year Plan (1985-90) and Draft Annual Plan 1985-86 (Volume III) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1985)
Local Artisans/skilled workers generally do not have the benefit of knowing the latest technological development of manufacturing methods in their respective field of activities. Use of improved tools, manufacturing processes, testing and quality trade are very much needed to upgrade the quality production of local small scale manufacturing units here. In order to provide such technical assistance, few artisans/skilled workers/entrepreneurs are selected to have advance training in various established institutions at mainland.
Andaman and Nicobar Administration
Andaman and Nicobar Administration